Korelasi antara Nilai HbA1c dengan Kadar Trigliserida Pasien Diabetes Mellitus Tipe 2 - Zulfian Zulfian Zulfian; Ika Artini; Rian Ardiva Barowalah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Diabetes mellitus (DM) is a disease or metabolic disorder with typical symptoms of hyperglycemia followed by carbohydrate, lipid and protein metabolic disorders caused by lack of insulin production or ineffectiveness of insulin, or it can occur simultaneously. The higher levels of sugar in the blood cause an increase in the enzyme lipoprotein lipase in adipose tissue, therefore increasing the level of triglycerides which can trigger the formation of sclerosis. To find the correlation between HbA1c values with triglyceride levels in patients with type 2 diabetes mellitus. This type of research is quantitative analytic correlative with a cross-sectional approach. The sample of this study was 49 people obtained from medical record data at Pertamina Bintang Amin Hospital in Bandar Lampung 2019. Respondents with a HbA1c value ≥9% were 31 people (63.3%), while respondents with a HbA1c value <9% 18 people (36.7%). Triglyceride levels for respondents ≥150 mg / dl 33 people (67.3%), while respondents with triglyceride levels <150 mg / dl 16 people (32.7%). From the Spearman test, there is a correlation between the HbA1c value with triglyceride levels in type 2 diabetes mellitus patients (p = 0.002). With (r = +0.439) which means the strength of the correlation is moderate. There is a correlation between HbA1c values with triglyceride levels in type 2 diabetes mellitus patients at Pertamina Bintang Amin Hospital in Bandar Lampung in 2019.